The bilirubin-to-albumin ratio as a potential prognostic biomarker for all-cause mortality in patients with acute decompensated cirrhosis: A prospective study - Hien Viet Quang Nguyen; Thang Viet Luong; Trung Nguyen Tran; Hai Nguyen Ngoc Dang (PLoS ONE, 2025)
Background Acute decompensation (AD) of liver cirrhosis is a life-threatening condition with high mortality and a significant healthcare burden. Although various prognostic models are available, their complexity often limits their practical utility in clinical settings. The bilirubin-to-albumin (B/A) ratio has emerged as a potential biomarker for critically ill patients. Despite its simplicity, the prognostic value of the B/A ratio in patients with AD remains uncertain. Methods This two-center, prospective observational study screened 748 participants. After follow-up and application of the exclusion criteria, 279 patients with AD were included in the final analysis. The B/A ratio was evaluated for its association with 30-day, 90-day, and 180-day mortality. Results Kaplan-Meier survival analysis demonstrated worse survival outcomes in patients with higher B/A ratios, with 180-day survival rates of 95.7%, 87.1%, 64.3%, and 56.5% from the lowest to highest quartiles, respectively. ROC curve analysis further validated its prognostic value, identifying optimal B/A ratio cutoffs of 3.30, 3.17, and 3.10 for predicting 30-day, 90-day, and 180-day mortality, with corresponding AUC values of 0.77, 0.79, and 0.75, indicating moderate predictive ability. The sensitivity and specificity at these cutoff points were 81.8% and 63.0% (30-day), 81.8% and 66.0% (90-day), and 77.9% and 68.7% (180-day). Furthermore, the B/A ratio demonstrated a prognostic performance comparable to MELD, MELD-Na, MELD 3.0, Child–Pugh, ALBI, EZ-ALBI, and PALBI, with no statistically significant differences in AUC values (p > 0.05). Conclusion The B/A ratio is a simple and effective prognostic biomarker, with a higher B/A ratio associated with increased mortality in patients with AD.